Hubungan Budaya Membaca Dengan Kemampuan Literasi Membaca Siswa Kelas VIII SMP Negeri 11 Kota Bengkulu: Hubungan Budaya Membaca Dengan Kemampuan Literasi Membaca Siswa Kelas VIII SMP Negeri 11 Kota Bengkulu - Maulani, Febianti Aisyah; Yulistio, Didi; Trianto, Agus (Jurnal Korpus, 2025)
Reading literacy is an essential competence in learning; therefore, examining its relationship with students’ reading culture is necessary. The purpose of this study is to describe thepractice of reading culture,to describe the ability to read literacy and to know the relationship between readingculture and the reading literacy ability of class VIII students  Junior High School State11 Bengkulu City. The method used in this study is a descriptive method with a quantitative approach. The population in this study was grade VIII students of Junior High SchoolState11 Bengkulu City. The sampling technique uses quota sampling with a total sample of 60 students. Data collection techniques and data research instruments use questionnaires and tests on reading literacy skills. Based on the results of data analysis, researchers can describe that the reading culture of class VIII students of Junior High SchoolState 11 Bengkulu City is included in the weak criteria and the reading literacy ability of grade VIII students of Junior High SchoolState11 Bengkulu City is included in the category of lack. Thecalculated r value is based on the results of research data analysis calculated using the product momentand SPSS correlation formula, which is 0.315. When compared to rtables, the results of rcounts>rtables with a significant level of 5% (0.315 > 0.254). The relationship between reading culture and the reading literacy ability of class VIII students in Bengkulu City. Based on the calculation of the coefficient of determination, reading culture contributes to reading literacy ability by 10% which means that the low influence of reading culture on students' reading literacy ability, researchers suspect that the instruments used in this study have not fully supported the results of the research conducted.